Co-channel Interference Monitoring based on Cognitive Radio Node Station - Arief Marwanto; M. Ulin Nuha; Jenny Putri Hapsari; Daniel Triswahyudi (IAES Indonesia Section, 2018)
Most of installation on wireless LAN on the building is not considering location and geographic space are which probable co-channel interference among near-far wi-fi stations. The use of the same channel which causes of receiver stations experiences of error transmission and delay among data transmission. To analyze this drawbacks, cognitive radio (CR) is adopted which able to monitoring co-channel interference on wi-fi stations. Node MCU Arduino is used to proposed cognitive radio terminal which able to analyzed and monitoring co-channel interference among wi-fi stations known as co-channel monitoring cognitive radio (CCMCR). One of the CR task is ability to sensing the whole spectrum channel that operated in certainty frequency. Node MCU is sensed the energy power of the wi-fi stations and converted by analog-to-digital converter which detected power level of the received signal strength indicator (RSSI). The proposed model is examined by indoor experiments which obtained 63.8% co-channel average and adjacent-channel is 36.1%. Thus the proposed CCMCR node station is able to monitor co-channel interference and adjacent-channel as well. Therefore, the results could be used as the basic analysis for the development and installation of wi-fi stations in the building.